Efectos de la exclusión de ganado sobre la calidad ambiental de un arroyo pampeano - Giorgi, Adonis David Nazareno (2014)
For two years, records of channel morphology and quality of the bank on a section of a stream were made because the cattle farming have been excluded at a section of 500 meters of long near the bank and 10 meters at each bank. There were registered also changes in the aquatic vegetation and some physico-chemical parameters. Fish sampling was conducted annually to observe species presence and their relative abundance. It was detected a rapid improvement in the quality of banks and an increase of the richness of fishes in each sample. Contrary to expectations macrophyte richness was reduced and morphological heterogeneity of the channel is not increased. However, the stream ceased to be interrupted and started having more water in the entire stretch. This was as a result of reshaping the banks. Although this register should be validated with future surveys, the results suggest that the recovery of the banks is very fast and the runway and the fish colonization are staggered. Despite this, there was a clear recovery at the studied reach, with the exclusion of cattle in the area as the unique management practice.